ANALISIS BUDAYA ORGANISASI TERHADAP KINERJA DI LINGKUP UMKM WILAYAH TAMANSARI, KOTA TASIKMALAYA - Heru Kurniawan; Moh. Ikhsan Kurnia; A.Latif Nugraha; Alya Fauziah Maulida (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2024)
Organizational culture is a system of values, norms and beliefs held by a group of people in an organization that differentiates it from other organizations. This definition can also be seen as a pattern of basic assumptions discovered or developed by a group of people as they interact with each other. Organizational culture can also be interpreted as the characteristics or guidelines implemented by each member of an organization or company. Micro, Small, Small and Medium Enterprises (UMKM) are independent productive business units, carried out by individuals or business entities in all economic sectors which greatly assist the process of recovery or improvement of the Indonesian economy. Therefore, play a very important role in the rate of economic growth in Indonesia. The title of this research is